The Improvement of Adolescents' Knowledge on Reproductive Health Through Health Counseling - Rahmawati, Dwi Ayu; Nasrum, Efa Kelya; Zakiah, Via; Jingsung, Julian; Sukmawati, Sukmawati (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The main purpose of this service activity is to increase adolescents' knowledge about reproductive health. This activity was held on December 12, 2024 at SMA Negeri 3 Kendari. The method of implementing community service is in the form of providing health education or counseling activities with the method of lectures and discussions or questions and answers about reproductive health with the stages of preparation, implementation, and closing. The results of community service include the age characteristics of respondents who are 16 years old (32%), 16 people (32%) who are 17 years old, and 18 people who are 18 years old (36%). The pre-test of adolescent knowledge showed that in the category of lacking, there were 36 people (72%), 9 people (18%), and 5 people (10%) who were good and after the posttest, the average knowledge of respondents in the good category was 42 people (84%) and adequate, namely 8 people (16%). The implementation of this counseling received a good response, as evidenced by the enthusiasm and willingness of the participants who came to the location to take part in the activity on time